Low-Income Mothers' Descriptions of Children's Injury-Related Events - Lise L. Olsen; Joan L. Bottorff; Parminder Raina; Jim Frankish (SAGE Publishing, 2015)
The purpose of this study was to examine how mothers with young children who were living in low-income households used discursive strategies to explain their children's injury and near-miss events. In-person interviews were conducted with 17 mothers and a discourse analytic approach was used to analyze the data. Mothers used a variety of discursive strategies to explain injury events including minimizing the nature of events and expressing tensions between responsibility and resistance. Mothers also described challenges related to predicting children's behavior and dealing with competing demands. These discursive strategies reflected how societal expectations that mothers are held to in terms of keeping children safe conflicted at times with the constraints experienced by mothers living in economically challenging situations. The findings can be used to inform the design of injury prevention strategies that are sensitive to experiences of mothers of young children who are living with economic challenges.